Two routes to actorhood: lexicalized potency to act and identification of the actor role - Frenzel, Sabine; Schlesewsky, Matthias; Bornkessel-Schlesewsky, Ina (Frontiers in Psychology, 2015)
The inference of causality is a crucial cognitive ability and language processing is no exception: recent research suggests that, across different languages, the human language comprehension system attempts to identify the primary causer of the state of affairs described (the "actor") quickly and unambiguously (Bornkessel-Schlesewsky & Schlesewsky, 2009). This identification can take place verb-independently based on certain prominence cues (e.g. case, word order, animacy). Here, we present two experiments demonstrating that actor potential is also encoded at the level of individual nouns (a king is a better actor than a beggar). Experiment 1 collected ratings for 180 German nouns on 12 scales defined by adjective oppositions and deemed relevant for actorhood potential. By means of structural equation modeling, an actor potential (ACT) value was calculated for each noun. Experiment 2, an ERP study, embedded nouns from Experiment 1 in verb-final sentences, in which they were either actors or non-actors. N400 amplitude increased with decreasing ACT values and this modulation was larger for highly frequent nouns and for actor versus non-actor nouns. We argue that potency to act is lexically encoded for individual nouns and, since it modulates the N400 even for non-actor participants, it should be viewed as a property that modulates ease of lexical access (akin, for example, to lexical frequency). We conclude that two separate dimensions of actorhood computation are crucial to language comprehension: an experience-based, lexically encoded (bottom-up) representation of actorhood potential, and a prominence-based, computational mechanism for calculating goodness-of-fit to the actor role in a particular (top-down) sentence context.